Higher triglyceride serum level increases atherosclerotic index in subjects 50-70 years of age - Mawi, Martiem; Chondro, Fransisca; Chudri, Juni (Universa Medicina, 2015)
BackgroundAtherosclerosis, the underlying cause of heart attack, stroke and peripheral disease, is a main cause of morbidity and mortality worldwide. Hypercholesterolemia and hypertriglyceridemia are independent factors in the development and progression of atherosclerosis. The atherosclerotic index (AI) is a strong indicator of cardiovascular heart disease. The objective of this study was to determine the relationship between lipid serum level and AI in subjects 50-70 years of age. Methods A study of cross-sectional design was conducted among male and female subjects 50-70 years of age. The inclusion criteria were: healthy, and capable of active communication. The exclusion criteria were: subjects not completing the study, currently consuming antihyperlipidemic drugs. Lipid profile comprising total cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL), triglycerides, and malondialdehyde (MDA), was analyzed using commercial kits. Systolic and diastolic blood pressure and body mass index was measured in all subjects. Atherogenic index was calculated from (total cholesterol â HDL cholesterol) / HDL cholesterol. Multiple linear regression was used to analyze the data.Results Mean age of the subjects was 60.6 Â± 3.30 years and there was a significant relationship of LDL cholesterol and triglycerides with AI (b=0.009; p=0.000 and b=0.008; p=0.000, respectively). Triglyceride level was the most influencing factor for AI (b=0.008; Beta=0.616; p=0.000)ConclusionsHigher triglyceride levels increase AI in subjects 50-70 years of age. Subjects with high serum triglyceride level but without symptoms of cardiovascular disease should be examined for the development of coronary artery blockage.